Application of Short Fiber Reinforced Composite Materials Multilevel Model for Design of Ultra-light Aerospace Structures. (2017) - Kurkin, E.I.; Sadykova, V.O.
Abstract: A Multilevel approach of modeling the stiffness and strength of ultra-light aerospace structures from short reinforced composite materials is presented. The object of the research is the strength elements of aerospace structures and specifically, the lugs for the transfer of concentrated forces in the gateway of unit places. The material is anisotropic. The properties of this material depend on the organization of the casting process of the plates from which the lugs are cut. The first level of the model is the descriptive model of the casting process of the plate from PEEK material. The casting model of plates is based on the geometry of the gating system and the tool geometry which defines the characteristics of the high-viscosity heat exchange, reinforced during binding with the environment. The preprocessor for the first level of model production is Moldex Designer, with which the geometrical characteristics of the gating system of heat exchange are set. The finite-element mesh for calculation of the hydrodynamic task is constructed. Calculation of casting process of the gate is carried out in Moldex 3D system. The initial data are the finite-element model, the parameters defining the casting mode: temperature, pressure, material volume, and also the parameters of modes of hold pressure and cooling of detail. The orientation of the file of fibers, which is used for the description of the anisotropy of the products considered is the result of casting modeling of the plate. The second level of the model is the model of anisotropic material with the characteristics defined taking the orientation of reinforcing fibers into account, obtained from the results of the casting process in the DIGIMAT system. The possibility of detailing the material characteristics received on the basis of the processing of strength tests of material samples is considered. The third level of model is the finite-element model of the product considering anisotropy of material. The model is constructed in the ANSYS Workbench system. The strength characteristics of the anisotropic material are defined in the model by the DIGIMAT module connected to ANSYS through the material parameter setting DIGIMAT Material. The multilevel model allows calculation of the strain-stress state of products of irregular shape cast from composite materials reinforced by short high-strength fibers. The results of the multilevel model production are verified with field research of the considered products.